Assessment of sex differences in bone deficits among adolescents with anorexia nervosa. Issue 4 (9th September 2016) - Nagata, Jason M.; Golden, Neville H.; Peebles, Rebecka; Long, Jin; Leonard, Mary B.; Chang, Audrey O.; Carlson, Jennifer L.
ABSTRACT: Objective: The objective of this study was to compare sex differences in bone deficits among adolescents with anorexia nervosa (AN) and to identify other correlates of bone health. Method: Electronic medical records of all patients 9–20 years of age with a DSM‐5 diagnosis of AN who were evaluated by the eating disorders program at Stanford with dual‐energy X‐ray absorptiometry (DXA) between March 1997 and February 2011 were retrospectively reviewed. Whole body bone mineral content Z ‐scores and bone mineral density (BMD) Z ‐scores at multiple sites were recorded using the Bone Mineral Density in Childhood Study (BMDCS) reference data. Results: A total of 25 males and 253 females with AN were included, with median age 15 years (interquartile range [IQR] 14–17) and median duration of illness 9 months (IQR 5–13). Using linear regression analyses, no significant sex differences in bone deficits were found at the lumbar spine, total hip, femoral neck, or whole body when controlling for age, %mBMI, and duration of illness. Lower %mBMI was significantly associated with bone deficits at all sites in adjusted models. Discussion: This is the first study to evaluate sex differences in bone health among adolescents with AN, using novel DSM‐5 criteria for AN and robust BMDCS reference data. We find no significant sex differences in bone deficits among adolescents with AN except for a higher proportion of females with femoral neck BMD Z ‐scores <‐1. Degree of malnutrition was correlated with bone deficits at all sites. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:352–358)